2010
DOI: 10.3109/13813455.2010.513392
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemotherapy-associated protein patterns in tumour tissue and serum of patients with metastatic renal cell carcinoma

Abstract: Individual prediction of therapy benefit and selecting patients for ICT based on molecular biological profiles appear to be feasible in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…SELDI-TOF's usefulness for biomarker discovery has been questioned for a number of reasons. There are instances in which investigators have not been able to reproduce results using different data sets [18][19][20], as was the case in our study; where different investigators detect unexpected biomarkers for the same disease [21][22][23], where there is failure to validate biomarkers using traditional methodologies [8], as in our study; and where validation studies detect the same biomarkers, but produce opposite results [24], as was suggested by some of our findings. Not surprisingly, most biomarkers lack sufficient disease specificity to work as stand-alone biomarkers [25,26].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…SELDI-TOF's usefulness for biomarker discovery has been questioned for a number of reasons. There are instances in which investigators have not been able to reproduce results using different data sets [18][19][20], as was the case in our study; where different investigators detect unexpected biomarkers for the same disease [21][22][23], where there is failure to validate biomarkers using traditional methodologies [8], as in our study; and where validation studies detect the same biomarkers, but produce opposite results [24], as was suggested by some of our findings. Not surprisingly, most biomarkers lack sufficient disease specificity to work as stand-alone biomarkers [25,26].…”
Section: Discussionsupporting
confidence: 51%
“…SELDI-TOF has yielded biomarkers for some cancers and other disorders, and has been used to determine patients' response to therapy [4]. Although there are a few validated SELDI-TOF derived biomarkers [5][6][7][8][9], most have not been validated using more traditional approaches such as Enzyme Linked Immunosorbent Assay (ELISA) or Western Blot.…”
Section: Introductionmentioning
confidence: 99%
“…This binding reagent allows for the separation of less abundant biomarkers from common proteins in the cell lysate as well as the use of unpurified samples (Figure 1) [45]. The monolayer of proteins and peptides formed in this method also allows for clearer signal detection [48]. SELDI-TOF has identified protein peaks for the diagnosis of a variety of cancers including breast cancer, hepatocellular carcinoma, and renal cell carcinoma, often with greater accuracy than current diagnostic methods [4,5,43,48].…”
Section: Emerging Protein Analysis Techniquesmentioning
confidence: 99%
“…Capillary electrophoresis then detects the released fluorescent tags [55,57]. This method uses formalin fixed paraffin embedded tumor specimens, the most common way of preserving solid tumor samples for analysis such as IHC [45,46,48]. …”
Section: Emerging Protein Analysis Techniquesmentioning
confidence: 99%